Corporate governance and firm performance among Shariah and non-Shariah approved companies in Malaysia / Mohd Ariff Mustafa - Mustafa, Mohd Ariff (2012)
This study attempts to analyze the trend of corporate governance and to investigate the relationship of corporate governance and firm performance among the Shariah and non-Shariah approved companies in Malaysia focusing on the elements of board independence, ownership structure, board size, CEO duality and board gender diversity. The motivation of the study is to see the implication of MCCG 2007 Revised Code toward the company's corporate governance and hence, boost up the company's performance among Shariah and non-Shariah approved companies in Malaysia. The data are gathered from the analysis of companies' annual reports for a sample of top 50 Shariah approved companies and top 50 non-Shariah approved companies based, on its market capitalization over a period of 2009 and 2010. The study employs t-test and regression analyses. The preliminary results of this study reveal that most Malaysian Shariah and non-Shariah approved companies have complied with the recommendation of the MCCG (2000) and MCCG (2007) Revised Code to have an effective of board size and separation of role as CEO and chairman. It is also found that there is a significant relationship between board sizes and CEO duality toward firm performance. In addition, board gender diversity also has a significant relationship with firm performance. On the other hand, there are no associations between board independence and ownership structure to firm performance. The findings of this study is hoped to provide significant contributions in highlighting the important issues regarding the performance of companies with regards to the influence of corporate governance.